Aeroelastic Control of Wind Turbine Blade Using Trailing-Edge Flap. Issue 5 (October 2014) - Li, Nailu; Balas, Mark J.
A mathematic rotating blade model is introduced in conjunction with periodic time-varying aerodynamic load, which is described by Beddoes-Leishman dynamic stall model. The consequent aeroelastic model is utilized to analyze blade dynamics and design control strategy for blade flutter suppression application. Aeroelastic stability of rotating blade is indicated by Floquet Theory, and the stability indications show good agreement with results of open-loop simulation test for critical flutter speed study. It's shown that the Adaptive Controller is capable of restraining flutter vibration with the actuation of the trailing-edge flap. The robustness and effectiveness of the controller are shown by closed-loop tests with a wide range of aerodynamic loads. The stability analysis proves the stability of the Adaptive Controller by the Adaptive Stability Theorem.